Adolescent Self-Injury Tendencies among High School Students: A Descriptive Study - Yola Amalia; Gian Sugiana Sugara; Nandhini Huda Anggarasari (Edupotensia Foundation, 2025)
This study aims to describe the levels and forms of self-injury among high school students in Tasikmalaya. A quantitative approach with a descriptive design was employed, involving 168 students from grade XI at eight public senior high schools selected through simple random sampling. The instrument used was the Deliberate Self-Harm Inventory (DSHI) developed by Gratz (2001), which demonstrated good reliability (α = 0.81). The findings showed that most participants (64.9%) were categorized as having low levels of self-injury, while 35.1% were in the moderate category, and none were in the severe category. Scratching was identified as the most common form of self-injury, followed by carving words or symbols on the skin and self-hitting. Further analysis revealed gender differences, with female students reporting significantly higher self-injury scores (M = 3.18, SD = 2.48) compared to males (M = 1.85, SD = 1.21), F(1,148) = 14.05, p < .001. Overall, the study highlights that self-injury behaviors among adolescents in Tasikmalaya tend to be at a low level but remain a concerning issue, particularly among female students. Preventive efforts and school-based counseling interventions are recommended to address this behavior.